2020
DOI: 10.1093/schbul/sbaa158
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Intensive Care Unit Admission and Mortality Among Patients With Schizophrenia and COVID-19: A National Cohort Study

Abstract: Patients with schizophrenia (SCZ) represent a vulnerable population who have been understudied in COVID-19 research. We aimed to establish whether health outcomes and care differed between patients with SCZ and patients without a diagnosis of severe mental illness. We conducted a population-based cohort study of all patients with identified COVID-19 and respiratory symptoms who were hospitalized in France between February and June 2020. Cases were patients who had a diagnosis of SCZ. Controls were patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 37 publications
2
87
3
1
Order By: Relevance
“…The prevalence of COVID-19 in people with comorbid schizophrenia is not dissimilar between the genders (49 and 51% for males and females, respectively), while women had higher death rates and less ICU admissions than men (13). This is discrepant to the general population, where male gender is a risk factor for ICU admission and mortality (31).…”
Section: Schizophrenia and Covid-19: Prognostic Factors And Potential Mechanisms Age Gender And Ethnicitymentioning
confidence: 87%
See 4 more Smart Citations
“…The prevalence of COVID-19 in people with comorbid schizophrenia is not dissimilar between the genders (49 and 51% for males and females, respectively), while women had higher death rates and less ICU admissions than men (13). This is discrepant to the general population, where male gender is a risk factor for ICU admission and mortality (31).…”
Section: Schizophrenia and Covid-19: Prognostic Factors And Potential Mechanisms Age Gender And Ethnicitymentioning
confidence: 87%
“…Schizophrenia appears to be associated with poorer prognosis in patients with COVID-19. A French population-based cohort study has reported a higher odds of mortality among in-patients with schizophrenia compared with controls [AOR 1.30 [95% CI, 1.08-1.56], P = 0.0093) (13). Another case-control study reported that patients with SMD including schizophrenia are 1.3 times more likely to experience severe outcomes (mortality, It is noteworthy that all the study estimates described above were adjusted for potential confounders, including age, gender and chronic medical comorbidities such as CVD, DM, COPD, cancer etc.…”
Section: Interaction Between Covid-19 and Schizophrenia: Epidemiological Evidencementioning
confidence: 99%
See 3 more Smart Citations